(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Acute toxicity of a buprofezin-based product (commercial product Elisa 440 SC) to pupae of the whitefly parasitoid Encarsia formosa Gahan (Hymenoptera: Aphelinidae), and its effects on life history traits and population growth in F1 generation of a commercial strain (“Dutch” strain, D) and two local populations from Serbia (Bujanovac, B; Negotin, N) were examined in laboratory bioassays. All trials were carried out at 27±1°C temperature and 60±10% relative humidity, and under 16/8 h daylight/darkness photoperiod in four replications. In an acute toxicity bioassay, tobacco leaves carrying parasitoid pupae (20 pupae per replicate) were treated with a series of buprofezin concentrations covering a 10-90% mortality range, and mortality was calculated based on the number of emerging adults 9 days after treatment. The following LC50 (mg/l) estimates were obtained: 244.2, 281.5 and 199.5 (for B, N and D, respectively). The product based on buprofezin, applied to parasitoid pupae at concentrations within the LC50s and 95% confidence limits (264 mg/l for B and N; 220 mg/l for D), significantly prolonged the duration of juvenile development (2, 1.7 and 2.2 days for B, N and D, respectively, compared to control data). Females from all tested populations that emerged from the treated pupae and were exposed to the residual action of buprofezin lived shorter than control females (B, N and D by 1.5, 0.7 and 1.7 days, respectively). Also, females that emerged from the treated pupae achieved a significantly reduced level of parasitism (B, N and D by 11.7, 17.7 and 17.6 %, respectively), total adult emergence (B, N and D by 11.6, 17.8 and 17.8 %, respectively) and instantaneous rate of increase (B, N and D by 8.2, 6.8 and 12.5 %, respectively), compared to control. More precise determination of risks involved in the use of buprofezin requires its more detailed field testing.